2021
DOI: 10.1111/infa.12435
|View full text |Cite
|
Sign up to set email alerts
|

Online measures of looking and learning in infancy

Abstract: Infants in laboratory settings look longer at impossible than possible events, learn better about objects that behave surprisingly, and match people's utterances to the objects that likely elicited them. The paradigms that reveal these behaviors have become cornerstones of research on preverbal cognition. But less is known about whether these canonical behaviors generalize in naturalistic environments. Here we describe a series of online protocols that replicate classic laboratory findings, detailing our metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Research conducted via video conferencing has used this visual preference method to probe early social evaluations (in situations that do not involve false beliefs), and found that looking and reaching measures converge in infants and toddlers (Woo & Spelke, 2022) (as reviewed above). Other research has used visual preference methods to probe toddlers' understanding of emotion, replicating in-lab findings (Smith-Flores et al, 2022). Across these in-lab and video-conferencing-based experiments, participants have not looked longer to events in which agents engaged in prosocial actions.…”
Section: Methodsmentioning
confidence: 93%
“…Research conducted via video conferencing has used this visual preference method to probe early social evaluations (in situations that do not involve false beliefs), and found that looking and reaching measures converge in infants and toddlers (Woo & Spelke, 2022) (as reviewed above). Other research has used visual preference methods to probe toddlers' understanding of emotion, replicating in-lab findings (Smith-Flores et al, 2022). Across these in-lab and video-conferencing-based experiments, participants have not looked longer to events in which agents engaged in prosocial actions.…”
Section: Methodsmentioning
confidence: 93%
“…For example, they could increase participant diversity, improve reproducibility and collaborative possibilities and reduce costs for researchers and participants. Moreover, recent infant studies have shown that lab studies can be replicated online (e.g., Chuey et al., 2021; Smith‐Flores et al., 2022). Hence, online testing can be a good option for infant research.…”
Section: Discussionmentioning
confidence: 99%
“…There are multitude benefits of an online platform, including the ability to efficiently run participants, to recruit more diverse participants, and to continue research during laboratory shut-downs, such as during the COVID-19 pandemic. There has been some success in validating the use of these platforms, including findings that experimental conclusions derived via this platform are comparable to those of in-lab studies ( Scott et al, 2017 ; Smith-Flores et al 2022 ). Note, however, that effect sizes appear to be smaller for online studies, which may also explain some of our smaller effects.…”
Section: Discussionmentioning
confidence: 99%